LARGe HR Management in the Fintech Disruptive Innovation Era - Moussallem, Elie (Digital Repository of Theses, 2025)
This study investigates the integration of the LARGe HRM framework and its impact on financial institutions’ human resource management (HRM) practices, particularly in the context of rapid technological advancements. The study explores how adopting the LARGe HRM framework and HR technology influences HR effectiveness, employee engagement, and satisfaction within the financial sector. Using a sample size of 105 employees from various organizations, including financial institutions, participants were selected through a stratified random sampling technique to ensure representation across different levels (Managers and employees) and departments (HR and Non-HR). Data were collected via a survey through Google Forms and analyzed using Excel and SPSS. When strategically integrated with human-centered HR practices, the findings suggest that HR technology adoption can support organizational goals, contribute to operational efficiency, and create a more engaged, satisfied, and high-performing workforce. These findings have practical implications for HR practitioners, providing insights into balancing technology adoption with employee-centric HR strategies in the financial sector. Keywords: LARGe HRM Framework, Disruptive Technology, Employee Satisfaction, Employee engagement, financial institutions, FinTech, Human Resource Management Practices.